Staphylococcus aureus Membrane-Derived Vesicles Promote Bacterial Virulence and Confer Protective Immunity in Murine Infection Models - Askarian, Fatemeh; Lapek, John D.; Dongre, Mitesh; Tsai, Chih-Ming; Kumaraswamy, Monika; Kousha, Armin; Valderrama, J. Andrés; Ludviksen, Judith A.; Cavanagh, Jorunn P.; Uchiyama, Satoshi; Mollnes, Tom E.; Gonzalez, David J.; et al. (Frontiers in Microbiology, 2018)
Staphylococcus aureus produces membrane-derived vesicles (MVs), which share functional properties to outer membrane vesicles. Atomic force microscopy revealed that S. aureus-derived MVs are associated with the bacterial surface or released into the surrounding environment depending on bacterial growth conditions. By using a comparative proteomic approach, a total of 131 and 617 proteins were identified in MVs isolated from S. aureus grown in Luria-Bertani and brain-heart infusion broth, respectively. Purified S. aureus MVs derived from the bacteria grown in either media induced comparable levels of cytotoxicity and neutrophil-activation. Administration of exogenous MVs increased the resistance of S. aureus to killing by whole blood or purified human neutrophils ex vivo and increased S. aureus survival in vivo. Finally, immunization of mice with S. aureus-derived MVs induced production of IgM, total IgG, IgG1, IgG2a, and IgG2b resulting in protection against subcutaneous and systemic S. aureus infection. Collectively, our results suggest S. aureus MVs can influence bacterial–host interactions during systemic infections and provide protective immunity in murine models of infection.